Civil-military relations: control and effectiveness across regimes - Bruneau, Thomas C.; Croissant, Aurel (Lynne Rienner Publishers, 2019)
"Explores how civilian control affects military effectiveness in democratic, hybrid, and authoritarian regimes"--
Keywords: Konferenzschrift -- 2018 -- Heidelberg; Fallstudiensammlung; Zivil-militärische Zusammenarbeit